2022
DOI: 10.3389/fgene.2022.845498
|View full text |Cite
|
Sign up to set email alerts
|

LDL-C Concentrations and the 12-SNP LDL-C Score for Polygenic Hypercholesterolaemia in Self-Reported South Asian, Black and Caribbean Participants of the UK Biobank

Abstract: Background: Monogenic familial hypercholesterolaemia (FH) is an autosomal dominant disorder characterised by elevated low-density lipoprotein cholesterol (LDL-C) concentrations due to monogenic mutations in LDLR, APOB, PCSK9, and APOE. Some mutation-negative patients have a polygenic cause for elevated LDL-C due to a burden of common LDL-C-raising alleles, as demonstrated in people of White British (WB) ancestry using a 12-single nucleotide polymorphism (SNP) score. This score has yet to be evaluated in people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Discordant results among different populations suggest that the polygenic score for LDL-c levels should be tailored to the genetic background of each population. In fact, ethnicity has been demonstrated to be relevant for the distribution of score values and for the association with LDL-c levels [20,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discordant results among different populations suggest that the polygenic score for LDL-c levels should be tailored to the genetic background of each population. In fact, ethnicity has been demonstrated to be relevant for the distribution of score values and for the association with LDL-c levels [20,43].…”
Section: Discussionmentioning
confidence: 99%
“…This score was then further refined to reduce the number of SNPs to 6 without losing its performance, according to the original study [17]. Different polygenic scores have been developed to meet the genetic background of different populations, highlighting that a single LDL-c score or a single cut-off cannot be universally used [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Novel lipid-lowering drugs, such as PCSK9 inhibitors, could be proposed, as Quagliariello [ 35 ] did, putting forward the argument that PCSK9 inhibition in patients with cancer treated with ICI therapies enables a reduction in atherosclerotic cardiovascular events and potentially improves ICs-related anticancer functions. This meta-analysis did not have the sensitivity to determine whether subjects who developed dyslipidemia under immunotherapy were carriers of a predisposing genetic mutation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gratton et al. (2022) [ 15 ] demonstrated that this PRS had better performance in individuals with UK Black and Caribbean and White ancestries than Asians individuals and proposed the hypothesis of the adoption of a specific-ethnic decile cut-off value than a general one. Likewise, as shown by Toft-Nielsen and colleagues [ 23 ], FH prevalence diverge among different ancestries, being more prevalent in Black and White than Asian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the replication of this PRS has already been carried out in at least 6 European countries, in Israel and Korea, and in all studies, the score was significantly associated with LDL-c values [ 13 , 14 ]. In addition, a recent study showed this score distribution and association with LDL-C in three different UK ethnic groups [ 15 ].…”
Section: Introductionmentioning
confidence: 99%